THE INTERNATIONALIZATION STRATEGIES OF INFORMATION TECHNOLOGY FIRMS FROM BRAZIL: DAN AHP ANALYSIS OF IVIA’S CASE - Mota, Márcio de Oliveira; Nogueira, Cláudio André Gondim; Ogasavara, Mário Henrique (Internext, 2012)
A large body of literature describes the internationalization process of diverse firms worldwide; however it is imperative to understand how firms from emerging countries behave when they decide to internationalize. This paper provides a comprehension of the main factors that increase the probability of success of the internationalization process of Information Technology – IT firms in Brazil according to three internationalization theories OLI, RBV and Networks. Ivia‟s case was selected and in-depth interviews were held with the three key Ivia executives. This research used the Analytic Hierarchy Process – AHP in order to evaluate the relative importance of factors and sub-factors proposed by the theories considered. The results indicated that Ivia‟s internationalization strategy focused primarily on the formation of strong and steady partnerships with foreign IT service providers, clients, and research and development institutions in order to seize opportunities abroad. The company exploited location advantages and resources, which include the international knowledge and experience of the top managers and the capability to satisfy its clients‟ specific needs through the development of customized products and services. The results may be useful to executives and researchers of strategic management and to those who want to study deeper this field.